Kualitas Layanan dan Citra Perusahaan Terhadap Kepuasan Pengguna Jasa Pelayanan Kesehatan RS Hermina Semarang - amalia, Reza; Putra, Harmanda Berima (Politeknik Piksi Ganesha Indonesia, 2025)
ABSTRACT The increasingly competitive health service competition requires hospitals to continue to improve the quality of service and strengthen the image of the institution in order to maintain patient satisfaction. This study aims to analyze the effect of service quality and corporate image on user satisfaction at Hermina Pandanaran Hospital, Semarang. This study uses a quantitative approach with 180 patients selected through purposive sampling techniques. Data collection was carried out through questionnaires, and data analysis used multiple linear regression with the help of SPSS version 23. The results of the study indicate that service quality and corporate image have a positive and significant effect on patient satisfaction. The dimensions of service quality assessed include reliability, empathy, assurance, and accessibility, while corporate image includes the values and personality of the institution. The average value of respondents shows a good perception of the hospital's service and reputation. This study concludes that consistent improvement in service quality and positive corporate image are key factors in creating patient loyalty and satisfaction. These findings can be a strategic basis for hospital management in improving services and maintaining public trust. ii. Keywords: service quality, corporate image, patient satisfaction, hospital